Handedness, Stuttering and Allergies - J Gordon Millichap (Pediatric Neurology Briefs)
The relationship of left-handedness to allergic disorders and stuttering, using epidemiological data of two French samples, is reported from L'Institut National de la Sante et de la Recherche Medicale, Villejuif, France.